1982
DOI: 10.1111/j.1748-1716.1982.tb06948.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of subcutaneous blood flow during head‐up tilt (45°) in normals

Abstract: Local and remote regulation of subcutaneous blood flow in the forearm and leg was studied during head-up tilt (45 degrees) in 6 young healthy male subjects. Relative blood flow was estimated by the local 133Xe washout technique. Lowering of a leg to a 51% decrease in its subcutaneous blood flow due to a veno-arteriolar reflex elicited by the increase in venous transmural pressure. During head-up tilt subcutaneous blood flow in the arm remaining at heart level decreased by 27%, in the leg blood flow decreased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 20 publications
(12 reference statements)
2
29
0
Order By: Relevance
“…U showed a rapid increase of calf volume (assessed by plethysmography) immediately upon head-up tilt.The shifted blood volume is located mainly in the venous vascular system leading to stretch on the venous vascular walls [6]. According to Skagen and Bonde-Petersen [26], Skagen et al [27], Henriksen et al [13] and Andersen et al [2] an increase of pressure by 25 mmHg in the venous vascular system will result in a 40-50 % increase in arterial vascular resistance via the VAR, which has been suggested by these researchers to run via a sympathetic nerve axon. It has also been shown that specific triggers, like bladder distension, lead to spinal sympathetic reflex activity and leg vasoconstriction [32].…”
Section: Discussionmentioning
confidence: 95%
“…U showed a rapid increase of calf volume (assessed by plethysmography) immediately upon head-up tilt.The shifted blood volume is located mainly in the venous vascular system leading to stretch on the venous vascular walls [6]. According to Skagen and Bonde-Petersen [26], Skagen et al [27], Henriksen et al [13] and Andersen et al [2] an increase of pressure by 25 mmHg in the venous vascular system will result in a 40-50 % increase in arterial vascular resistance via the VAR, which has been suggested by these researchers to run via a sympathetic nerve axon. It has also been shown that specific triggers, like bladder distension, lead to spinal sympathetic reflex activity and leg vasoconstriction [32].…”
Section: Discussionmentioning
confidence: 95%
“…Skagen and Bonde-Petersen (1982) showed that proximal nervous blockade in healthy human subjects can block the vasoconstriction in the arms but not in the legs, indicating that leg vasoconstriction is not induced by centrally mediated sympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
“…The shifted blood volume is located mainly in the venous vascular system leading to stretch on the venous vascular walls (Buckey et al 1988). An increase in pressure of 25 mmHg in the venous vascular system will result in a 40-50% increase in arterial vascular resistance via the veno-arteriolar reflexes, which runs via a sympathetic axon (Andersen et al 1991;Henriksen et al 1983;Skagen and Bonde-Petersen 1982;Skagen et al 1982b;Skagen and Henriksen 1983). However, against the hypothesis of veno-arteriolar reflexes or spinal sympathetic reflex activity (the latter normally induced by specific triggers like pain and bladder distension rather than by head-up tilt; Webborn 1998) seems to be the fact that noradrenaline hardly shows an increase in P individuals (Mathias et al 1975) suggesting that the activity of the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…local circulatory control; axon reflex WHEN VENOUS PRESSURE in a limb is elevated to pressures Ͼ25 mmHg, cutaneous, subcutaneous, and muscle vascular resistances increase within that region, resulting in a reduction in blood flow of ϳ40% (2,5,16,17,31,32). This reflex has been termed the venoarteriolar response (VAR), because stretch receptors reported to be located in small veins are hypothesized to cause changes in arteriolar vascular tone "upstream" of the veins (15).…”
mentioning
confidence: 98%